Simulasi Numerik Model Arus Lalu Lintas dengan Pengaruh Kepadatan Kendaraan dan Kondisi Jalan - Nashrul Millah (Contemporary Mathematics and Applications (ConMathA), 2023)
Traffic jams are common in developing countries. This is generally caused by traffic density, road conditions, and the driver's personality. This phenomenon can be simulated using a mathematical model, allowing it to be seen how these factors affect traffic conditions. The goal of this study is to simulate the effect of traffic density and road conditions using the Lighthill-Whitham-Richard (LWR) model. This model is used to describe macroscopic traffic flow conditions, which are affected by traffic density and speed. The Greenshield model with the influence of road condition parameters added is used for the speed. In numerical solutions, the Upwind method is used to evaluate midpoint values. The simulation results demonstrate the model's ability to describe traffic conditions that are affected by traffic density and road conditions. The level of traffic density is inversely proportional to road conditions and traffic speed.